Efeitos da abreviação do jejum em indivíduos submetidos à colecistectomia: uma revisão sistemática com metanálise - Campos , Samara Bomfim Gomes (2017)
Considering that the practice of preoperative fasting is based on observations regarding delayed gastric emptying after anesthetic induction and this time is linked to the organic response to trauma, the question arises about the preoperative fasting period necessary to minimize this response and support professional practice on scientific evidence. Clinical studies have been designed to evaluate gastric emptying and the effect of fasting time on the organic response to trauma. The literature indicates that the fasting abbreviation with a carbohydrate (CHO) enriched beverage up to 2 hours before the surgical procedure can bring benefits to clinical and metabolic parameters, besides not offering a risk of bronchoaspiration in healthy subjects submitted to elective surgeries. Aiming to contribute to this discussion, this dissertation presents two articles: a narrative review, with a bibliographical survey about the metabolic implications of fasting in surgical trauma, gastric emptying physiology, safety, benefits and the recommendations of the fasting abbreviation. The second article is a systematic review with meta-analysis from randomized clinical trials, with the objective of evaluating the effect of preoperative fasting with CHO on insulin resistance and postoperative nausea in Individuals submitted to cholecystectomy, compared to traditional fasting or placebo (PLA) with water. The search carried out in the PubMed, Scielo and Cochrane Library databases until December 2016, without time restriction. The texts needed at least to have title and abstract in english, spanish or portuguese. The primary outcome was IR and secondary nausea. In studies that met the eligibility criteria, bias risk analysis was performed. The calculation of the weighted mean difference was applied, with the attribution of the weight of the studies by the inverse variance method and calculation by the random effect model for the RI outcome. For the nausea outcome, the Mantel-Haenzel method was used, with the relative risk measurement. In case of high heterogeneity, a subgroup analysis was performed. Among the 769 studies found in the databases, 9 met the eligibility criteria. In the general analysis, for both variables, there was no difference between CHO versus PLA/control treatments, ((mean difference, 95% CI (-0.16 (-0.75 to 0.44), I2 = 92%, P = 0.61) and (relative risk, 95% CI (0.86 (0.65 to 1.12), I2 = 59%, P = 0.26)), respectively. In the subgroup analysis of the outcome RI, CHO versus fasting, the RI was reduced in the CHO group (mean difference, 95% CI (-0.61 (-0.80 to -0.42), I2 = 0%, P <0.01) while in the analysis, CHO versus PLA, RI was reduced in the PLA group (mean difference 95% CI (0.60 (0.28 to 0.92), I2 = 11%, P <0.01). In both subgroup analyzes of the nausea outcome there was no difference between CHO versus fasting and CHO versus PLA treatments ((relative risk, 95% CI (0.92 (0.63 to 1.34), I2 = 68%, P = 0.32) and (relative risk , 95% CI (0.79 (0.49 to 1.27), I2 = 59%, P = 0.32)), respectively. Ingestion of CHO beverage reduces postoperative RI in patients undergoing cholecystectomy. Despite the ingestion of PLA versus CHO, further studies need to be performed to elucidate the mechanisms involved and their benefits. Regarding the occurrence of nausea, the ingestion of CHO or control did not benefit the reduction of this intercurrence.